PENGARUH PENGGUNAAN MEDIA BERBASIS EDUTAINMENT TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPS KELAS 4 SDN BENCONGAN 6 - Khoirunnisa, Firda; Sunardin, Sunardin; Perdiansyah, Ferry (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to compare social studies learning outcomes between students who used edutainment media and students who used conventional learning methods. This study used a quasi-experimental with a research design of Nonequivalent Control Group Design. Children in grade 4 at SDN Bencongan VI became the population in this study. There were 2 classes totaling 70 children as samples of this study, namely class IVB as the control class and class IVC as the experimental class. Learning outcomes were used as the main data in the data collection strategy, which was supported by test questions. In the control class and experimental class, the results of hypothesis testing using the t test at the end of learning (posttest) resulted in tcount = 3.81 with a significance level of 5% (= 0.05). ttable = 2.03 was obtained and Ho was rejected because 3.81> 2.03 (tcount> ttable). Based on the results of the study, it can be concluded that there is a relationship between the use of edutainment media with student learning outcomes in social studies subjects in class IV.